Cooperation and Competition Among Automated Vehicles in Highway Merge Scenario—A Proof-of-Concept Study - Eugene Lee; Joonho Park; Kitae Jang; Eunjeong Ko; Zhibin Li; Jaehyun So (IEEE Access)
This study compares strategies for controlling the specific movements of automated vehicles by applying concepts of cooperation and competition in a highway merge scenario. To enhance understanding, each concept was first analyzed from a sociological perspective. Based on this analysis, cooperation in the context of automated vehicles was characterized by the key terms “common goal/benefit, shared ownership of resources, and interaction”, while competition was characterized by “individual goal/benefit, personal ownership of resources, and individual actions”. Reflecting these key terms, the objective of cooperation was to optimize system cost, whereas the objective of competition was to optimize individual cost. Simulations were conducted to implement the movements of automated vehicles, and a dynamic programming model was used to predict and optimize vehicle trajectories. The results were analyzed in terms of mobility and safety metrics. Vehicles in the cooperation scenario, due to system-level optimization, maintained speed distributions centered around 90 km/h in the Main segment and 80 km/h in the merge segment. Competitive vehicles showed broader distributions with speeds peaking at 85-90 km/h and 75-80 km/h, respectively. In terms of safety, the cooperative approach recorded 26 conflicts in the merge segment compared to 33 in the competitive scenario, while achieving higher time-to-collision (TTC) values and lower deceleration rates (4.3 m/s2 vs. 5.7 m/s2). These results highlight the advantages of the cooperative approach in optimizing both mobility and safety.